Designing Interactive Learning Application Using Markerless Augmented Reality on Chemical Bonds Material - Adilla Rizka Yonita; Guspatni (Perspektif Ilmu Pendidikan, 2023)
The era of industrial revolution 4.0 has changed and affected our lives, including in education. One of the technologies that had a significant impact was the smartphone. Smartphones can be a learning media that helps students clarify concepts, create enthusiasm for learning, and provide new and interesting experiences. This research aims to design a learning application integrated with marker-less augmented reality for chemical bond materials. Chemical bonds are one of the abstract concepts in chemistry, making it challenging for students to understand. This study follows an educational design research approach using the Plomp development model. Based on preliminary research and prototype stages, the design of this learning application has successfully run well according to the plan through self-evaluation and has produced prototype II. Therefore, it is hoped that this learning media, in the form of an application, will support learning activities in schools.